Traditional African Vegetables - Guarino, Luigi; International Plant Genetic Resources Institute (1997)
Many species of African traditional vegetables are poorly known, being used only locally. They are difficult subjects for conventional agronomic study, often being cultivated in small patches in domestic gardens or growing as weeds in marginal areas within farms or wild in forest areas. However, they are extremely important for nutrition and farm income throughout Africa, often supplying most of the daily requirements for vitamins A, B complex and C [ascorbic acid] of rural people. A series of papers are presented in two sections: conservation and use strategies (3 papers); and diversity and traditional uses of African vegetables (23 papers). A key aim of this workshop was to develop a regional strategy for the conservation and use of genetic resources of traditional vegetables in Africa and, to this end, a series of recommendations have been formulated and are presented. A list of workshop participants and abbreviations used are included. (Abstract © CAB ABSTRACTS, CAB International)